THE EFFECT OF RESIDENTIAL ROOM CONFIGURATION ON NATURAL VENTILATION OF RUSUN UNITS TO ACHIEVE LOW ENERGY BUILDING - Megan Afkasiga Ririhena; Nedyomukti Imam Syafii (ASEAN Journal of Systems Engineering, 2021)
Rusun is a simple flat categorized as Affordable Housing (AH), which means it requires economic energy efficiency and optimal Natural Ventilation (NV) to manifest and provide comfort for users. This research will review the effect of spatial configuration on NV conditions of Rusun unit in terms of the condition of wind flow (WF) and wind speed (WS) value in each residential room by simulation method.The condition of the unit is on the 10th floor and height of 31.5m with an outdoor WS of 1.62 m/s in three different space configurations. It was found from the simulation that residential space that has direct access from openings both inlet and exit (outlet) has a more optimal WF and WS. From the WF condition and WS value following the needs of residential user activities, it is expected to optimize NV in Rusun units and in line with that, can realize energy-efficient Rusun buildings in terms of occupancy.